2002
DOI: 10.1046/j.1462-2920.2002.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobial position as a main determinant in the problem of competition for nodulation in soybean

Abstract: Selected Bradyrhizobium japonicum strains inoculated on soybean seeds often fail to occupy a significant proportion of nodules when a competitor rhizobial population is established in the soil. This competition problem could result from a genetic/ physiological advantage of the adapted soil population over the introduced inoculant or from a positional advantage, as the soil population already occupies the soil profile where the roots will penetrate, whereas the inoculant remains concentrated around the seeds. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
20

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 31 publications
3
43
0
20
Order By: Relevance
“…Thus, the identification of conditions that are a determinant for competitiveness of the inoculated rhizobia is an important goal. We proposed that the position of rhizobia in the soil profile in relation to the roots and the rhizobial motility in the soil might be two of these conditions (López‐García et al , 2002). Further studies by Kanbe et al (2007) and Althabegoiti et al (2008) indicated that B. japonicum possesses two different flagella.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the identification of conditions that are a determinant for competitiveness of the inoculated rhizobia is an important goal. We proposed that the position of rhizobia in the soil profile in relation to the roots and the rhizobial motility in the soil might be two of these conditions (López‐García et al , 2002). Further studies by Kanbe et al (2007) and Althabegoiti et al (2008) indicated that B. japonicum possesses two different flagella.…”
Section: Introductionmentioning
confidence: 99%
“…They include the ability of rhizobia to utilize specific carbon and energy sources [17,18], the overall metabolic potential of bacteria [19], bacteriocin production, resistance to bacteriocin [20], the susceptibility to plant molecular signals [21,22] and bacterial motility [23]. In addition, the legume hosts themselves [24][25][26] and the distribution of rhizobia in the soil [27] may also influence the outcome of competitive interactions between rhizobia. Furthermore, it is possible that compounds other than plant-derived flavonoids and rhizobial Nod factors may influence strain competitiveness for nodule occupancy in Rhizobiumlegume interactions [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Commercial inoculants for soybean have been found to contain high levels of NolA (Loh et al 2001). When B. japonicum cells are cultured in N-starved media, the production of exopolysaccharides, capsular polysaccharides and the expression of nodC:lacZ is reduced, which results in the production of reduced nodule number by older cultures, or in delayed nodule formation in younger culture (Lopez-Garcia et al 2001 greenhouse experiments demonstrated that N-starvation during culture of an effective rhizobia strain did not enhance their competitiveness against an established and less competitive strain (Lopez-Garcia et al 2002), suggesting that number and position are more important than genetic/physiological aspects of competitiveness for inoculated strains. Using nod gene expression to indicate Nod factor production, Loh and Lopez-Garcia's experiments (Loh et al 2001;Lopez-Garcia et al 2001) demonstrated that although Nod factor production by a culture increased as cell density increased, production per cell decreased.…”
Section: Nod Factor Quorum Sensing and Its Relevance To Inoculant Promentioning
confidence: 99%